Replacing coal in Georgia's power plants with woody biomass to increase carbon benefit: A mixed integer linear programming model - Masum, Farhad Hossain; Wang, Weiwei; Colson, Greg; Dwivedi, Puneet (Journal of environmental management, 2022)
To combat climate change, reducing carbon emissions from coal consumption in the power sector can be an effective strategy. We developed a price-exogenous mixed integer linear optimization model satisfying both traditional timber demand in Georgia and its neighboring states (Alabama, Florida, North Carolina, South Carolina, and Tennessee) and additional bioenergy demand to replace coal in the power plants of Georgia for 50 years, maximizing social welfare. We used Forest Inventory & Analysis unit level yield of five forest types (planted softwood, natural softwood, upland hardwood, bottomland hardwood, and mixed forest), timber demand, and price information, and developed three scenarios. In the Baseline scenario, traditional annual timber demand (152 million tons of wood) was satisfied with no coal replacement. In Scenario 1, 100% coal (7.34 million tons annually) was replaced using pulpwood only, along with traditional demand. In Scenario 2, also with traditional demand, 100% coal was replaced using pulpwood and logging residues. It would require approximately 336 and 98 thousand acres of additional annual timberland harvested in Scenario 1 and Scenario 2, respectively, compared to Baseline (1280 thousand acres). During 50 years, a total of 9.3, 10.2, and 9.6 billion tons of timber was produced in Baseline, Scenario 1, and Scenario 2, respectively. About one-third of all torrefaction plants would be located in the central region of Georgia. The net change in stand carbon was positive in all three scenarios—the highest in Baseline (1330 million tons C), followed by Scenario 2 (1261 million tons C), and the lowest in Scenario 1 (872 million tons C). About 240 million tons of carbon was avoided by using biomass instead of coal in Scenario 1 and Scenario 2. In Baseline, with continued emission from coal usage in the power plant for 50 years (285 million tons C), net carbon benefit was 1046 million tons C. Replacing 100% of coal with both pulpwood and logging residues provided a net benefit of 1501 million tons C, about 43% higher compared to baseline. [Display omitted] •1.28 million acres of forest harvested annually from 6 states without biopower.•Forestland harvest can reach up to 1.62 million acres with biopower.•75 torrefaction plants will be required to meet Georgia's biopower demand.•Bioenergy demand in Georgia will be primarily satisfied by Georgia and Alabama.•Replacing coal with pulpwood and logging residue yields the highest carbon benefit.